Integrated residential childcare – facilitators and barriers for collaboration between residential care and mental health care: a systematic review - Timonen-Kallio, Eeva; Kraav, Siiri-Liisi; Kaittila, Anniina; Leinonen, Leena; Alin, Minna; Karukivi, Max; Anis, Merja (Taylor & Francis Group, 2026)
The severe mental health problems of the many youths living in out-of-home care place demands on integrated care between the residential childcare (RCC) sector and the mental health care sector. Thus, all available resources and the professional expertise of both sectors must be coordinated to ensure adequate care. This is problematic as research highlights that reconciling the different working cultures and professional intentions of the residential childcare and mental health care sectors is perceived as difficult. As such, the purpose of this systematic review is to synthesize the evidence from studies on facilitators and barriers of integrated care practices. A literature search, limited to articles published in English between 2016 and 2022, was conducted of seven databases. Seven studies were included in the review. Information-sharing systems, structured models and joint training are suggested as bases for promoting integrated care. Interestingly, although the frontline practitioners in the residential care and mental health care sectors (social educators, nurses, care workers, etc.) play a crucial role in the implementation of integrated care, research on inter-sectoral and indeed inter-professional care is scarce. More detailed research on the factors that facilitate integrated residential care is needed. This knowledge is valuable, particularly in the Nordic high-level training system, as it reflects how we should promote inter-professional learning processes and internships to better understand and appreciate the capabilities and priorities of other professionals and service providers to ensure better outcomes for youth. This review has implications for staff standards and for residential childcare workers’ professional competencies.